Integrating community health volunteers into non-communicable disease management among Syrian refugees in Jordan: a causal loop analysis. Issue 4 (20th April 2021) - Parmar, Parveen K; Rawashdah, Fatma; Al-Ali, Nahla; Abu Al Rub, Raeda; Fawad, Muhammad; Al Amire, Khaldoun; Al-Maaitah, Rowaida; Ratnayake, Ruwan
Abstract : Objectives: Globally, there is emerging evidence on the use of community health workers and volunteers in low-income and middle-income settings for the management of non-communicable diseases (NCDs), provision of out-of-clinic screening, linkage with health services, promotion of adherence, and counselling on lifestyle and dietary changes. Little guidance exists on the role of this workforce in supporting NCD care for refugees who lack access to continuous care in their host country. The goals of this work were to evaluate the current roles of community health volunteers (CHVs) in the management of diabetes and hypertension (HTN) among Syrian refugees and to suggest improvements to the current primary care model using community health strategies. Setting and participants: A participatory, multistakeholder causal loop analysis workshop with representatives from the Ministry of Health of Jordan, non-governmental organisations, United Nations agencies, CHVs and refugee patients was conducted in June 2019 in Amman, Jordan. Primary outcome: This causal loop analysis workshop was used to collaboratively develop a causal loop diagram and CHV strategies designed to improve the health of Syrian refugees with diabetes and HTN living in Jordan. Results: During the causal loop analysis workshop, participants collaboratively identified and mapped how CHVs might improve care among diagnosed patients. Possibilities identified included the following: providing psychosocial support and foundational education on their conditions, strengthening self-management of complications (eg, foot checks), and monitoring patients for adherence to medications and collection of basic health monitoring data. Elderly refugees with restricted mobility and/or uncontrolled disease were identified as a key population where CHVs could provide home-based blood glucose and blood pressure measurement and targeted health education to provide more precise monitoring. Conclusions: CHV programmes were cited as a key strategy to implement secondary prevention of morbidity and mortality among Syrian refugees, particularly those at high risk of decompensation.